Performance analysis of OFDM-PSK system for optimization of fiber optic dispersion - Ibrahimy, Muhammad Ibn; Akhter, Fowzia; Siddiquei, Hasin Reza (EuroJournals Publishing, Inc., 2011)
The Performance of Orthogonal Frequency Division Multiplexing (OFDM)combined with Phase Shift Keying (PSK) has been analyzed in presence of fiber optic dispersion. The influence of dispersion on the OFDM spectrum is investigated with fiber lengths, bit rates and source linewidths. The inter-channel interference occurs due to dispersion-induced broadening of OFDM spectrum. The power penalty suffered by the system is evaluated at bit error rate, BER=10-9 for a single mode fiber operating at 1.55μm. The results obtained from the OFDM-PSK have been compared with OFDM-QAM system. The obtained results demonstrate that the influence of dispersion is lower on OFDM-PSK spectrum in comparison with OFDM-QAM spectrum having same bandwidth.